Ischemic Preconditioning Modulates the Peripheral Innate Immune System to Promote Anti-Inflammatory and Protective Responses in Mice Subjected to Focal Cerebral Ischemia - Amantea, Diana; La Russa, Daniele; Frisina, Marialaura; Giordano, Francesca; Di Santo, Chiara; Panno, Maria Luisa; Pignataro, Giuseppe; Bagetta, Giacinto (Frontiers in Immunology, 2022)
The development of tolerance triggered by a sublethal ischemic episode (preconditioning, PC) involves a complex crosstalk between neurons, astrocytes and microglia, although the role of the peripheral immune system in this context is largely unexplored. Here, we report that severe cerebral ischemia caused by transient middle cerebral artery occlusion (MCAo) in adult male mice elevates blood counts of inflammatory neutrophils and monocytes, and plasma levels of miRNA-329-5p. These inflammatory responses are prevented by ischemic PC induced by 15 min MCAo, 72h before the severe insult (1h MCAo). As compared with sham-operated animals, mice subjected to either ischemic PC, MCAo or a combination of both (PC+MCAo) display spleen contraction. However, protein levels of Ym1 (a marker of polarization of myeloid cells towards M2/N2 protective phenotypes) are elevated only in spleen from the experimental groups PC and PC+MCAo, but not MCAo. Conversely, Ym1 protein levels only increase in circulating leukocytes from mice subjected to 1h MCAo, but not in preconditioned animals, which is coincident with a dramatic elevation of Ym1 expression in the ipsilateral cortex. By immunofluorescence analysis, we observe that expression of Ym1 occurs in amoeboid-shaped myeloid cells, mainly representing inflammatory monocytes/macrophages and neutrophils. As a result of its immune-regulatory functions, ischemic PC prevents elevation of mRNA levels of the pro-inflammatory cytokine interleukin (IL)-1β in the ipsilateral cortex, while not affecting IL-10 mRNA increase induced by MCAo. Overall, the elevated anti-inflammatory/pro-inflammatory ratio observed in the brain of mice pre-exposed to PC is associated with reduced brain infarct volume and ischemic oedema, and with amelioration of functional outcome. These findings reaffirm the crucial and dualistic role of the innate immune system in ischemic stroke pathobiology, extending these concepts to the context of ischemic tolerance and underscoring their relevance for the identification of novel therapeutic targets for effective stroke treatment.